FOOD WASTE AND RELIGIOUS HOLIDAYS: An Examination of Ethics And Sustainable Practices from An Interfaith Perspective - Ali, Iqmi Qaisah; Kuswanjono, Arqom; Prasetianti, Isnaeni Gelda (Universitas Islam Indonesia, 2025)
Food waste, particularly during major religious celebrations like Ramadan and Christmas, often results from excessive consumption, lack of planning, and social traditions that elevate the potential for waste. This phenomenon has a detrimental impact on the environment due to the increased volume of food waste. This study aims to explore food waste during religious holidays through a qualitative approach and literature review. The analysis reveals that religious teachings from Islam, Christianity, and Buddhism offer ethical solutions to reduce food waste. Islam emphasizes balance and the prohibition of extravagance (israf), Christianity highlights humanity’s role as stewards of God's creation, and Buddhism promotes mindfulness in consumption. By integrating religious values with sustainable practices, religious communities can transform their celebrations into opportunities for social and environmental harmony. The study underscores the significance of an interfaith approach to mitigating food waste and promoting sustainability.